Game behavior to carbon reduction of enterprises in the industrial symbiosis chain under different reciprocal scenario - ZHANG Kaixuan, DING Lili (Ziyuan Kexue, 2023)
[Objective] Aiming at addressing the issue of insufficient enterprises’ carbon emission reduction power of industrial symbiosis chain, and based on the reciprocity preference theory, this study explores the game decision making between upstream and downstream enterprises of industrial symbiosis chain. It examines the influencing factors, mechanism, and effect of carbon reduction of industrial symbiosis chain, to provide a decision-making basis for environmental policy makers. [Methods] Considering the reciprocity preference behavior of upstream and downstream enterprises, this paper starts with two scenarios of direct reciprocity and indirect reciprocity, an evolutionary game model of industrial symbiosis chain enterprises’ emission reduction under government intervention was established. Using the Matlab 2019b software, this study simulates and analyzes the sensitivity of influencing factors. [Results] (1) When the government strictly regulates, the symbiosis probability of upstream and downstream enterprises increases, and vice versa. (2) The direct reciprocity preference can promote enterprises’ carbon emission reduction of industrial symbiosis chain. Relative income distribution contract and cost sharing contract have more significant promoting effect on the symbiosis of the upstream and downstream enterprises in the industrial symbiosis chain. (3) Indirect reciprocity preference also has a positive impact on carbon emission reduction behavior of industrial symbiosis chain enterprises. The influence of cost-sharing and benefit-sharing contracts on the symbiosis strategy of upstream enterprises is symmetrical, that is, when the cost sharing exceeds a certain threshold, the non-symbiosis probability of upstream enterprises increases, while the impact of benefit-sharing contracts is opposite. However, the effect of cost-sharing and benefit-sharing contracts on downstream enterprises' symbiosis strategy is not significant. [Conclusion] The study concluded that the increase of government regulation, reciprocity preference coefficient and income-sharing coefficient, together with the decrease of cost-sharing coefficient would all have an impact on manufacturers’ enthusiasm for carbon emission reduction. This study puts forward relevant countermeasures and recommendations for improving enterprises reciprocal cooperation system of industrial symbiosis chain in terms of effective government supervision, establishment of contract mechanism and reputation mechanism, to better encourage enterprises to reduce emissions.